Kajian Literatur: Granul Instan dari Bahan Alam Sebagai Antioksidan - Rahadatul Aisy Chaniago (Lembaga Pengembangan Kinerja Dosen, 2023)
Instant granules are preparations in the form of granules that are served by brewing and are widely chosen because of their practicality. Natural materials are widely used as antioxidants, but they still need to be made practical for their use. Therefore, this literature review was conducted to provide information regarding the formulation, evaluation of instant granules, and natural ingredients used in instant granules. This research method was carried out by studying literature from various data sources, namely the Directory of Open Access Journals, Science Direct (DOAJ), Garuda, and Google Scholar. A literature search was carried out using several keywords such as